Queer binge: harmful alcohol use among sexual minority young people in Australia. (February 2020) - Demant, Daniel; Saliba, Bernard
Abstract: Objectives: The literature suggests that sexual minority young people (SMYP) use alcohol at disproportionate levels when compared with their heterosexual counterparts. Little is known about alcohol dependency symptoms and correlations between high-risk alcohol use/dependency symptoms and minority stress in this population in general and between subgroups. Study design: Cross-sectional study. Methods: Descriptive statistics, adjusted odds ratios, and analysis of covariance were used to determine high-risk alcohol use, dependency symptoms, differences between subgroups, and correlations between alcohol use, dependency symptoms, and minority stress. Results: A total of 1556 Australian SMYPs aged 18 to 35 years completed the survey. Fifty percent of the participants reported high-risk alcohol consumption with significant differences between subgroups. Typical dependency symptoms such as 'health, social, legal or financial problems due to alcohol consumption' (16.8%, n = 247) were identified in large parts of the sample. High-risk consumption and dependency symptoms were significantly correlated with minority stress. Conclusion: High levels of high-risk alcohol use and dependency symptoms were found, largely consistent with existing literature. However, disparities are not distributed equally in this population, suggesting that future health promotion interventions should focus on SMYP subgroups. Significant correlations between minority stress and dependency symptoms/high-risk use suggest a potential route for future interventions in these populations. Highlights: 51.2% of participants engaged in high-risk alcohol use. High prevalence of alcohol dependency symptoms. Gay men and bisexual people more likely to use alcohol at high-risk levels. High-risk use and dependency symptoms correlate with minority stress.